Acquisition of English Tense and Agreement Morphology by Speakers of Malaysian Languages - Wong, Bee Eng (2010)
This paper reports on a study that investigates the acquisition of English tense and agreement morphology by Malaysian ESL (English as a Second Language) learners. These learners speak Malay and Chinese. In other words, they are Malaysian L1 Malay and L1 Chinese speakers Df L2 English. The Failed Functional Features Hypothesis (Hawkins and Chan, 1997) serves as the framework fDr the study. The hypothesis claims that post-childhood L2 learners experience syntactic deficits in the L2 if specific parameterised features present in the functional categDries of the L2 are not specified in the L1, However, selected L1 features that correspDnd to L2 settings are able to enter L2 syntactic derivations. In terms of form-meaning relationships, it is predicted that a syntactic deficit resulting from an L1 influence will affect the assignment of native-like meanings to surface forms. And depending Dn the differences in the L1 and L2, learners from different L1 backgrounds will not shDW similar patterns of develDpment The study gathered data from the two groups Df ESL learners in an attempt to compare the role played by the Chinese and Malay languages in the acquisition of the English property investigated. A grammaticality judgement task (comprising both grammatical and ungrammatical items) was designed to test the learners' underlying knowledge of tense and agreement morphology in English. The task comprised 16 correctly inflected items, 16 items with omission of inflections, auxiliaries and copula, 16 wrDngly inflected items and 8 items with overgeneration of the be form. The findings suggest that apparent near native-like acquisition of the L2 property might not be the case when learners seem to have more difficulty with the ungrammatical items than the grammatical items. The findings Df such a study have pedagogical implications for the ESL (English as a Second Language) classroom.